Teachers’ Strategies in Online Speaking Class at Junior High School in Malang - Tursini, Umi; Triani, Ayu Sintya (Actual Insight, 2023)
For students, mastering English communicative skills is difficult. The COVID-19 pandemic has forced students to study online. Teachers must be able to adapt and present online learning strategies that suit the needs of students. This study aimed to find out the teachers’ teaching strategies and to explore the teachers’ difficulties in implementing teaching strategies in online speaking class at junior high school in Malang. A descriptive qualitative design in the form of a case study was used as the research design. The participants involved in this study were three English teachers at Kartika IV-8 Middle School Malang and Taman Siswa Malang Junior High School. Two instruments used in this study include observation and interviews. The data analysis process included data condensation, data display and drawing and verification of conclusions. The results of this study indicated that teachers used a variety of online speaking class teaching strategies such as discussion, simulation, and asking questions. The teachers also experienced several obstacles in implementing strategies in online speaking classes. In group discussions, teachers found it difficult to manage time and monitor student activities. The internet connection made it difficult for the teachers. In the simulation strategy, it was also difficult for teachers to monitor and assess student work. The teachers also found problems when applying the questioning strategy. This strategy could not be followed by all students. As a result, other students tended to be silent.